Role of base fluid on the thermal conductivity of oleic acid coated magnetite nanofluids - Lenin, Ramanujam; Joy, Pattayil Alias (COLLOIDS AND SURFACES A-PHYSICOCHEMICAL AND ENGINEERING ASPECTS, 2017)
Thermal conductivity enhancement of nanofluids of oleic acid coated magnetite nanoparticles dispersed in four different base fluids (toluene, xylene, mesitylene, kerosene) is studied to understand the role of the solvent (base fluid). From the correlation of the thermophysical properties of the base fluid with the thermal conductivity of the corresponding nanofluid, it is found that the nanofluid with the base fluid of lower intrinsic thermal conductivity and dielectric constant shows relatively larger enhancement in the thermal conductivity. A linear increase in the thermal conductivity with increasing viscosity is observed for all four nanofluids studied. The concentration dependent thermal conductivity studies showed enhancement only above a particular concentration, within the sensitivity of the measurement, and this critical concentration is different for the different nanofluids. The nanofluid with kerosene showed the lowest critical concentration for thermal conductivity enhancement compared to the other nanofluids. The difference between the experimental thermal conductivity and the calculated value using the Maxwell model is found to depend on the critical concentration. By assuming the critical concentration as the zero concentration, it is found that all the studied nanofluids almost follow the Maxwell model of thermal conductivity. Thus, for the dispersions of the same oleic acid coated magnetite nanoparticles, the base fluid affects the critical concentration for thermal conductivity enhancement, probably due to the interfacial effects arising from the surfactant-solvent interactions.
Keywords: Brownian-Motion; Enhancement; Heat-transfer Characteristics; Magnetic nanofluids; Maxwell model; Nanoparticles; Particle Migration; Size; stability; Suspension; Temprature; Thermal conductivity; Thermophysical properties; transport mechanism; viscosity